Characterization of the hemolytic activity of Staphylococcus aureus strains associated with toxic shock syndrome. - Chow, A W (1983)
The hemolytic activity of 32 vaginal isolates of Staphylococcus aureus from patients with typical toxic shock syndrome (TSS) was contrasted with that of 50 vaginal isolates from patients without TSS, using a standardized inoculum (10(5) CFU) on 5% sheep blood agar after 48 h of incubation under 30% CO2. Additionally, 7 nongenital isolates from patients with nonmenstrual TSS and 57 strains of nongenital control isolates were included for comparison. Vaginal TSS strains were significantly less hemolytic than non-TSS S. aureus strains of either genital (P less than 0.001) or nongenital (P less than 0.01) origin. Vaginal TSS S. aureus strains were also less hemolytic than were nongenital TSS S. aureus strains (P less than 0.02). This reduced hemolytic activity of genital TSS S. aureus strains may provide a useful marker for screening and further delineation of toxigenic S. aureus associated with menstrually related TSS.